2021
DOI: 10.4142/jvs.2021.22.e71
|View full text |Cite
|
Sign up to set email alerts
|

Basic reproduction number of African swine fever in wild boars (Sus scrofa) and its spatiotemporal heterogeneity in South Korea

Abstract: Background African swine fever (ASF) is a hemorrhagic fever occurring in wild boars ( Sus scrofa ) and domestic pigs. The epidemic situation of ASF in South Korean wild boars has increased the risk of ASF in domestic pig farms. Although basic reproduction number (R 0 ) can be applied for control policies, it is challenging to estimate the R 0 for ASF in wild boars due to surveillance bias, lack of wild boar population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…To the best of our knowledge, there are significant studies on the disease growth rate and basic reproduction number in suidae [57,[62][63][64][65][66][67] but spatial growths have not considered. In the present study, we applied an approach to analyze the spatial proliferation of ASFV in South Korea based on logistic growth parameters.…”
Section: Plos Onementioning
confidence: 99%
“…To the best of our knowledge, there are significant studies on the disease growth rate and basic reproduction number in suidae [57,[62][63][64][65][66][67] but spatial growths have not considered. In the present study, we applied an approach to analyze the spatial proliferation of ASFV in South Korea based on logistic growth parameters.…”
Section: Plos Onementioning
confidence: 99%
“…As wildlife, wild boar and ASFv-positive wild boar carcasses are increasing concerns of the risk of spillover of ASFv between wild boar to domestic pigs [ 4 24 25 ]. The detection and identification of wild boars using the 3D depth camera and AI model seems also to be very useful technology.…”
Section: Discussionmentioning
confidence: 99%
“…Although the expansion of ASF toward the southwest appears to be contained [31], concerns have been raised regarding a spread toward southeast regions along geographical fasttracks. Te forested Taebaek mountains, which run from north to south and are a highly favourable habitat for wild boar, are located in the eastern region of the Korean peninsula, providing a reservoir zone as a source of ASFV [25,32,36]. In addition, due to mountain elevations above 1,000 m on average, carcass detection and depopulation are challenging, which favours persistence in the environment.…”
Section: Risk Factors and Spatiotemporal Distributionsmentioning
confidence: 99%
“…In addition, due to mountain elevations above 1,000 m on average, carcass detection and depopulation are challenging, which favours persistence in the environment. ASFV is thus highly likely to spread south more rapidly through these mountain ranges [32,36]. Te predictive study of ASF in wild boar in Gangwon province, where most of the Taebaek mountain ranges are located, showed that a high risk of ASF-positive carcasses is distributed along the mountain ranges in the western and southwestern parts of the province, whereas the risk of ASF-positive hunted wild boar is distributed in western regions of the Taebaek mountain range in the central part of the province [25].…”
Section: Risk Factors and Spatiotemporal Distributionsmentioning
confidence: 99%
See 1 more Smart Citation